Application of Genomics Tools in Wheat Breeding to Attain Durable Rust Resistance - Babu, Prashanth; Baranwal, Deepak Kumar; Harikrishna,; Pal, Dharam; Bharti, Hemlata; Joshi, Priyanka; Thiyagarajan, Brindha; Gaikwad, Kiran B.; Bhardwaj, Subhash Chander; Singh, Gyanendra Pratap; Singh, Anupam (Frontiers in Plant Science, 2020)
Wheat is an important source of dietary protein and calories for the majority of the world's population. It is one of the largest grown cereal in the world occupying over 215 M ha. Wheat production globally is challenged by biotic stresses such as pests and diseases. Of the 50 diseases of wheat that are of economic importance, the three rust diseases are the most ubiquitous causing significant yield losses in the majority of wheat production environments. Under severe epidemics can lead to food insecurity threats amid the continuous evolution of new races of the pathogens, shifts in population dynamics and their virulence patterns, thereby rendering several effective resistance genes deployed in wheat breeding programs vulnerable. This emphasizes the need to identify, characterize and deploy effective rust-resistant genes from diverse sources into pre-breeding lines and future wheat varieties. The use of genetic resistance has been marked as eco-friendly and to curb the further evolution of rust pathogens. Deployment of multiple rust-resistance genes including major and minor genes in wheat lines could enhance the durability of resistance thereby reducing pathogen evolution. Advances in Next-Generation Sequencing (NGS) platforms and associated bioinformatics tools has revolutionized wheat genomics. The sequence alignment of the wheat genome is the most important landmark which will enable genomics to identify marker-trait associations, candidate genes and enhanced breeding values in genomic selections (GS) studies. High throughput genotyping platforms have demonstrated their role in the estimation of genetic diversity, construction of the high-density genetic maps, dissecting polygenic traits and better understanding their interactions through GWAS (genome-wide association studies) and QTL mapping, and isolation of R genes. Application of breeder’s friendly KASP assays in the wheat breeding program has expedited the identification and pyramiding of rust-resistance alleles/genes in elite lines. The present review covers the evolutionary trends of the rust pathogen and contemporary wheat varieties, and how these research strategies galvanized to control the wheat killer genus Puccinia. It will also highlight the outcome and research impact of cost-effective NGS technologies and cloning of rust resistance genes amid the public availability of common and tetraploid wheat reference genomes.